PEMASARAN AYAM BROILER MENINGKATKAN KEUNTUNGAN PETERNAK MELALUI EFISIENSI DAN STRATEGI PEMASARAN: SEBUAH TINJAUAN LITERATUR - Siti Saadatu Daroen; Nopita Sari Hutabarat; Faldi Satrya Akbarullah; Liisa Firhani Rahmasari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Broiler chickens are a livestock industry activity that focuses on meat production. The increasing population means the demand for broiler chickens increases from year to year. This increase in consumption and demand has become a business opportunity for broiler chicken breeders to develop their business through market development. However, until now there are still problems regarding the marketing of broiler chickens, namely the marketing chain is too long so that the profits obtained by farmers are less and less efficient. The objectives of this literature review are to: (1) determine the marketing channel chain in broiler chicken farming;(2) identifying the efficiency of marketing channels in broiler chicken farms on the profits of broiler chicken farmers; (3) determine the effect of marketing strategy on the profits of broiler chicken farmers. The method used is a literature review by searching data using Google Scholar, Scopus, PubMed, Crossref and using the help of journal article search tools, namely publish or perish. The results of the literature review show that the broiler chicken marketing chain can increase farmers' profits, by focusing on efficiency and strategic analysis. Shorter canal chains tend to provide greater profits for farmers. An effective marketing strategy can also increase farmers' profits, by considering the company's internal and external factors. Value chain analysis is also important to understand the overall marketing process for broiler chickens. Designing the right marketing strategy can help farmers maximize their profits. Collaboration between business actors is needed to develop the broiler chicken marketing value chain in order to improve regulations, supervision and market information.